Characteristics of clinical trials of influenza and respiratory syncytial virus registered in ClinicalTrials.gov between 2014 and 2021 - Lora, David; García-Reyne, Ana; Lalueza, Antonio; Maestro de la Calle, Guillermo; Ruíz-Ruigómez, María; Calderón, Enrique J.; Menéndez-Orenga, Miguel (Frontiers in Public Health, 2023)
The randomized clinical trial (RCT) is the ideal and mandatory type of study to verify the effect and safety of a drug. Our aim is to examine the fundamental characteristics of interventional clinical trials on influenza and respiratory syncytial virus (RSV). This is a cross-sectional study of RCTs on influenza and RSV in humans between 2014 and 2021 registered in ClinicalTrials.gov. A total of 516 studies were identified: 94 for RSV, 423 for influenza, and 1 for both viruses. There were 51 RCTs of RSV vaccines (54.3%) and 344 (81.3%) for influenza virus vaccines (p < 0.001). Twelve (12.8%) RCTs for RSV were conducted only with women, and 6 were conducted only with pregnant women; for RCTs for influenza, 4 (0.9%) and 3, respectively. For RSV, 29 (31%) of the RCTs were exclusive to people under 5 years of age, and 21 (5%) for influenza virus (p < 0.001). For RSV, there are no RCTs exclusively for people older than or equal to 65 years and no phase 4 trials. RCTs on influenza virus and RSV has focused on vaccines. For the influenza virus, research has been consolidated, and for RSV, research is still in the development phase and directed at children and pregnant women.